Cuidado enfermero en el perioperatorio de cirugías de rodillas en el adulto mayor: una revisión bibliográfica - Pilamunga Guamán, Leonardo Sebastián (2025)
Nursing care in the perioperative period of knee surgeries in the elderly is of great importance nowadays, due to an increase in life expectancy of the Ecuadorian population, which consequently leads the nursing staff to apply optimal care based on scientific evidence to help the patient's recovery during the 3 stages of the perioperative period; Similarly, an objective was established which was to propose a protocol to improve nursing care in the perioperative period of knee surgeries in the elderly in Ecuador based on a systematic review of the literature, for which a qualitative method was used to describe and evaluate different aspects regarding nursing care with different perceptions in order to obtain conclusions; This resulted in obtaining a protocol focused on the perioperative period for knee surgeries in the elderly, in addition to identifying care used by other nursing professionals that can be replicated in Ecuador and, as a conclusion, it will help reduce complications in the perioperative period, which will also reduce the patient's hospital stay.